Occupational Disease At Air Pollution, Electric Motors, Health - Siti Aisyah Umayyah (PT. Anagata Sembagi Education, 2024)
This writing aims to understand the concept of PAK, examine the causes and risk factors of PAK, understand the spectrum of diseases associated with PAK, and know how to detect PAK early. The benefits include a source of information and insight for readers about the concept of PAK, reading and reference material for students and the community, as well as a source of knowledge in the field of OSH in the workplace. As a result, this paper is expected to contribute to increasing understanding and awareness of the importance of OHS in creating a safe and healthy work environment.